2017
DOI: 10.1002/jrs.5154
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational investigation of pressure‐ and temperature‐induced phase transitions in metal formates templated by ethylammonium ions

Abstract: We report for the first time phonon properties of [CH3CH2NH3][Mg(HCOO)3] (EtAMg). The studied compound undergoes two structural temperature‐induced phase transitions and temperature‐dependent Raman and infrared studies let us to obtain insight into mechanism of these transitions. In particular, very large broadening of infrared and Raman bands, attributed to vibrations of the NH3 groups, revealed highly dynamic nature of these groups in the both high‐temperature phases. This result indicates that the phase tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The known formates have been extensively studied in a broad temperature range, and these studies showed that majority of them undergo phase transitions associated with orientational ordering of organic cations located in the cavities of the framework . Pressure is another thermodynamic parameter that can help to better understand structure–property relationship in this class of compounds . For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The known formates have been extensively studied in a broad temperature range, and these studies showed that majority of them undergo phase transitions associated with orientational ordering of organic cations located in the cavities of the framework . Pressure is another thermodynamic parameter that can help to better understand structure–property relationship in this class of compounds . For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression . Furthermore, application of pressure may lead to discovery of novel polymorphs that are not thermodynamically stable at ambient conditions . We have decided, therefore, to study high‐pressure behaviour of recently discovered acetamidinium manganese formate ([CH 3 C(NH 2 ) 2 ][Mn(HCOO) 3 ], AceMn), using Raman spectroscopy because this method is well‐known to be a very valuable tool in high‐pressure studies due to its sensitivity to changes in dynamics and structure of molecular units …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They report for the first time phonon properties of [CH 3 CH 2 NH 3 ][Mg (HCOO) 3 ] (EtAMg). The studied compound undergoes two structural temperature‐induced phase transitions and temperature‐dependent Raman, and IR studies allowed them to obtain insight into mechanism of these transitions . Du et al described the effect of C 70 rotation on the photoluminescence spectra of compressed C 70 *mesitylene.…”
Section: High Pressure and Temperature Studiesmentioning
confidence: 99%
“…The studied compound undergoes two structural temperature-induced phase transitions and temperature-dependent Raman, and IR studies allowed them to obtain insight into mechanism of these transitions. [202] Du et al described the effect of C 70 rotation on the photoluminescence spectra of compressed C 70 *mesitylene. They report a high-pressure study on a typical solvated fullerene, C 70 *mesitylene, using the diamond anvil cell technique with associated spectroscopic measurements.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%